2018
DOI: 10.4314/njt.v36i4.35
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of wind speed for electrical power generation in some selected sites in northern Nigeria

Abstract: In this paper, statistical analysis is carried out to determine the accurate frequency distribution that fits wind speed data. The frequency distributions used include Weibull, Rayleigh and Gamma distribution functions. The performances of the probability distributions are based on the error evaluations between the predicted and the theoretical wind power densities of the site. The Results show that Weibull distribution modelled the wind speed better compared to other distribution functions. According to the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The parameters of the Weibull distribution function consist of the scale parameter and shape parameter. The Weibull PDF, CDF, and QF are given below in (2) to (4), respectively [3,13,14]. In (3), when the scale parameter and the wind speed are equal, ( ) becomes about 0.632.…”
Section: ) Overview Of Parametric Distribution Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of the Weibull distribution function consist of the scale parameter and shape parameter. The Weibull PDF, CDF, and QF are given below in (2) to (4), respectively [3,13,14]. In (3), when the scale parameter and the wind speed are equal, ( ) becomes about 0.632.…”
Section: ) Overview Of Parametric Distribution Functionsmentioning
confidence: 99%
“…The Wakeby distribution function parameters consist of the location parameter, first and second scale parameters, and the first and second shape parameters. The Wakeby PDF is given in (11) [5,10,14], while the Wakeby CDF given in (12) is the inverse of the Wakeby QF given in (13) [5,6,14].…”
Section: ) Overview Of Parametric Distribution Functionsmentioning
confidence: 99%
“…Once a distribution does not observe the normality test, [23] suggested that the option inferential statistic was to use multivariate GARCH with its error distribution assumptions with fixed degree of freedom.…”
Section: Descriptive Test Statistic For Normality Testmentioning
confidence: 99%
“…Statistical studies have shown that the twoparameter gamma distribution is adequate to describe the distribution of surface wind speeds almost everywhere in Europe [28]. The probability density function and the cumulative function of the 2-parameter generalized Gamma distribution are given by equations ( 13) and ( 14), respectively.…”
Section: The Two-parameter Gamma Distribution Functionmentioning
confidence: 99%